1984
DOI: 10.1080/00288233.1984.10430635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lime on pasture production on soils in the North Island of New Zealand

Abstract: The literature on the use of lime (ground limestone) in New Zealand pastoral agriculture is reviewed, and the need for an objective assessment of accumulated results from Ministry of Agriculture and Fisheries field experiments is established. A data base consisting of records from 126 pastoral lime trials in the North Island of New Zealand is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
(6 reference statements)
1
15
0
Order By: Relevance
“…The current method for calculating lime requirements in pastoral soils (Edmeades et al 1984), based on the relationship between soil pH and response to lime, has severe limitations mainly because this relationship is rather poor (Sinclair 1995) and is derived empirically rather than from knowledge of the underlying mechanisms of acidification. The incorporation of a mechanistic model for predicting soil acidification rates into the current lime requirement method is expected to enhance the accuracy of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…The current method for calculating lime requirements in pastoral soils (Edmeades et al 1984), based on the relationship between soil pH and response to lime, has severe limitations mainly because this relationship is rather poor (Sinclair 1995) and is derived empirically rather than from knowledge of the underlying mechanisms of acidification. The incorporation of a mechanistic model for predicting soil acidification rates into the current lime requirement method is expected to enhance the accuracy of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…The yield response from both these grazing trials was higher than that reported from 38 mowing trials on North Island sedimentary soils (Edmeades et al 1984).…”
Section: No P Treatmentmentioning
confidence: 88%
“…Since soil pH in the high lime treatment was elevated above that required for optimum pasture growth (Edmeades et al 1984) for at least 10 years, then the yield response would have been expected to last longer than the first three years. In the first three years, the response in annual yield to high lime compared with no lime was from a response in grass yield.…”
Section: No P Treatmentmentioning
confidence: 98%
See 2 more Smart Citations